DETERMINATION OF WEAK EARTHQUAKE FOCAL MECHANISMS AND MODERN GEODYNAMICS OF SOUTHERN IRAN - Yu. L. Rebetsky; A. A. Lukk; R. E. Tatevossian; V. V. Bykova (Геодинамика и тектонофизика)
The Southern Iran territory, including the Zagros region and the margins of the Arabian and Eurasian plates, is a seismically active area with large industrial facilities of Iran. In this respect, studying modern geodynamics of this area is a top research task. This article presents a part of the studies conducted by the IPE RAS Seismological Expedition led by the Doctor of Physics and Mathematics S.S. Arefiev in 1999–2001. The research team studied the seismic setting on the construction site of the Bushehr Nuclear Power Plant. The main results discussed in the present article are the focal mechanism solutions based on the data of the IPE RAS seismic network. The network was deployed in the junction area of the Fars and Dezful tectonic provinces (north of the Bushehr NPP) and covered an area of 100´100 km. A specific feature of the seismic network was that it comprised local networks, and each local station was focused, first of all, on determining the precise locations of earthquake epicenters in a particular section of the crust. However, the scarcity of stations in such local networks and the technologies available at that time did not allow us to determine the mechanisms of earthquake foci. This problem was solved by integrating the seismological and tectonophysical methods. In the analysis, we used the tectonophysical approach that is usually applied to reconstruct stresses from the data on slickensides. This approach is based on a specific algorithm of the kinematic method developed by O.I. Gushchenko, which is used in the absence of sliding direction signs. It became possible, in addition to a few signs from the first P-wave arrivals (1–2 confident signs), to use the data on the S-wave polarization direction. By applying the Gushchenko algorithm to such data, the areas of P and T axes were quite reliably localized on a single hemisphere for determining the focal mechanisms. The focal mechanisms computed for 72 earthquakes correspond to the Kazerooni-Borazdzhan shearing zone and, at the same time, are indicative of the presence of crust incision mechanisms in the Bushehr Peninsula. The focal mechanisms computed in our study, as well as the mechanisms reported in the Global CMT Project Catalogue, show that the Bushehr Peninsula is located near the western boundary of the zone of strike-slip faults, which extends from the north (Zagros) to the south (the Persian Gulf) and widens as a horsetail-shape structure. In the crust of the Persian Gulf coast, the intensity of the strike-slip component in the earthquake focal mechanism is minimal. The earthquake mechanisms in this region are mainly related to thrusting, reverse faulting and even the crust incision.